Perbedaan Jenis Pelarut Terhadap Aktivitas Antioksidan Ekstrak Daun Lamtoro (Leucaena leucocephala (Lam.) de Wit) - Emelda emelda; Ade Lia Putri; Abdul Rahman Lubis; Alvina Fitriya Dewi; Ani Octaviani; Bariqna'im Katon Haryanggita (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
Lamtoro leaves (Leucaena leucocephala) have long been a traditionally used plant because they are rich in nutrients and have several health benefits. Antioxidants are compounds that can protect organisms from oxidation and free radicals, which are factors that cause cell damage. This study aims to determine the IC50 value and antioxidant activity of 70% ethanol extract and acetone extract from lamtoro leaves. The extraction of lamtoro leaves was carried out using the soaking method with 70% ethanol solvent and acetone solvent, respectively. The antioxidant activity test was carried out by determining the free radical inhibitory activity of DPPH (2,2-diphenyl-1-picrylhydrazyl). Absorbance measurements were carried out using a UV-Vis Spectrofotometer at a wavelength of 517 nm. 70% ethanol extract and acetone extract of lamtoro leaves have very strong antioxidant activity with IC50 values of 41.18 ppm and 3,87 ppm, respectively. This result is the same as the comparison, namely vitamin C, which also has very strong antioxidant activity with IC50 value of 1.42 ppm. The conclusion of this research is that the acetone extract of lamtoro leaves have very strong antioxidant activity because they are still in the range of less than 50 ppm.